ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI GELOMBANG BAGI SISWA SEKOLAH DASAR - Azri Naila Andini; Ramadanta Sinulingga; Adi Nugraha; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of digital technology has changed the learning paradigm, including the teaching of wave material in Natural and Social Sciences (IPAS) in elementary schools. This study aims to identify types of learning media, analyze their characteristics, and analyze their effectiveness in helping students understand the concept of waves. This study used a descriptive qualitative approach with a literature review method. Data were obtained from ten relevant scientific literature sources and analyzed using content and thematic analysis techniques. The results indicate that technology-based media such as interactive animated videos, Phet simulations, Augmented Reality (AR), and interactive Google Slides are highly effective in enhancing student understanding due to their visual, exploratory, and interactive nature. In contrast, conventional media such as posters and student worksheets are considered less effective due to their limitations in facilitating active student participation. This study recommends that teachers continue to develop skills in selecting and creating contextual and innovative learning media. Support from educational institutions is also crucial in providing facilities and training to make IPAS learning more engaging and meaningful.